First report of hexabothriid monogeneans from Australian carcharhinids - Vaughan, David B.; Couchman, Brennan A.; Hansen, Haakon; Trujillo-González, Alejandro (Zootaxa, 2026)
Herein, detailed supplementary descriptions and novel nucleotide sequences are provided for Heteronchocotyle leucas Hargis and Erpocotyle carcharhini Watson & Thorson (Monogenea: Hexabothriidae). This is the first report of a hexabothriid from an Australian carcharhinid (Elasmobranchii: Carcharhiniformes: Carcharhinidae) and the first record of these hexabothriid species from Australia, constituting new host records. Heteronchocotyle leucas is reported from Carcharhinus leucas (Valenciennes), C. amboinensis (Müller & Henle) and Negaprion acutidens (Rüppell), whereas E. carcharhini is reported from C. leucas and C. amboinensis, all from off the Capricorn coastline, Queensland. Heteronchocotyle leucas demonstrated significant size range differences in multiple measurement variables in populations from different hosts suggesting that worms could adapt in size to the different gill microhabitat architecture of different hosts species. A strong statistical positive correlation (p < 0.05) in the size of most sclerite variables of sclerite pairs 1A, 1B and 2B with the growth of H. leucas was demonstrated, indicating that sucker sclerites grow as the worm grows but that the functional shape of these sclerites is conserved. The three smallest sclerites of H. leucas, 2A, 3A and 3B demonstrate less correlation with growth, especially with the sclerite hook, which develops first. This suggests that these three sclerite pairs develop functionality early in the ontogeny of the worm post host-invasion but become increasingly redundant with increased growth, as the main sclerites develop. This is also supported by the haptoral musculature, which is minimal in these smallest sclerites but considerable in the others. Details of the reproductive system of H. leucas are provided that were incorrectly interpreted in the type-description. Heteronchocotyle leucas and E. carcharhini 28S molecular sequences are provided for the first time. The phylogenetic position of H. leucas and E. carcharhini within the Hexabothriidae, based on 28S sequences, is explored and briefly discussed.